USP5 Promotes Metastasis in Non-Small Cell Lung Cancer by Inducing Epithelial-Mesenchymal Transition via Wnt/β-Catenin Pathway - Xue, Sudong; Wu, Wei; Wang, Ziyan; Lu, Guangxian; Sun, Jiantong; Jin, Xing; Xie, Linjun; Wang, Xiaoyu; Tan, Caihong; Wang, Zheng; Wang, Wenjuan; Ding, Xinyuan (Frontiers in Pharmacology, 2020)
Ubiquitin-specific protease 5 (USP5) is a deubiquitinating enzyme that functions as an oncoprotein in a variety of human cancers. However, the expression and role of USP5 in the metastasis of non-small cell lung cancer (NSCLC) have not been addressed. In this study, we examined the expression and prognostic significance of USP5 in NSCLC. The results revealed that USP5 was overexpressed and correlated with metastasis and overall survival in NSCLC tissues. A further in vitro study revealed that the levels of USP5 protein in NSCLC cells were associated with epithelial–mesenchymal transition (EMT) markers. Furthermore, USP5 overexpression significantly enhanced, whereas USP5 silencing significantly decreased the expression of EMT proteins and migration and invasion of NSCLC cells. In addition, the results from western blotting demonstrated that USP5 regulated EMT via the Wnt/β-catenin signaling pathway. Further immunohistochemical analysis revealed that USP5 was significantly associated with the expression of β-catenin and EMT markers in NSCLC tissues. Overall, USP5 upregulation is associated with tumor metastasis and poor prognosis in patients with NSCLC. USP5 promotes EMT and the invasion and migration of NSCLC cells. Therefore, USP5 may serve as a novel prognostic biomarker and provide a potential target for the treatment of metastasis in NSCLC.